Asymmetric total synthesis of dihydroisocoumarins: 6-methoxymellein, kigelin and fusarentin 6, 7 dimethyl ether by employing proline catalysed asymmetric α-aminoxylation. Issue 46 (13th November 2020) - Markad, Sachin B.; Mane, Baliram B.; Waghmode, Suresh B.
Abstract: A concise asymmetric total synthesis of dihydroisocoumarins such as 6-methoxymellein, kigelin and fusarentin 6, 7-dimethyl ether in high enantiopurity have been achieved from non-chiral aldehydes by employing proline catalysed asymmetric α-aminoxylation reaction. The required stereochemistry of hydroxyl group have been generated by alternating L or D proline as a organocatalyst in α-aminoxylation step and lactone ring is assembled by oxa-Pictet-Spengler cyclisation reaction as the key steps. Graphical abstract: Image 1 Highlights: A concise total synthesis of dihydroisocoumarins. High enantiopurity. Proline catalysed asymmetric α-aminoxylation reaction.